1997
DOI: 10.1074/jbc.272.51.32042
|View full text |Cite
|
Sign up to set email alerts
|

Lipase Activities of p37, the Major Envelope Protein of Vaccinia Virus

Abstract: p37, the major protein of the extracellular enveloped form of vaccinia virus, is involved in the biogenesis of the viral double membrane and in egress of virus from the cell. p37 was expressed as a glutathione S-transferase fusion protein and was purified to homogeneity by silver staining using glutathione-agarose, Sephacryl S-200, and DEAE-cellulose chromatography. Incubation of p37 with phosphatidylcholine labeled in the fatty acyl side chains resulted in the production of multiple lipid products that were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…Loss of the A56 or A33 protein did not affect this phenomenon. The F13 protein has sequence similarity to mammalian phospholipase (PL) D and has PL activity to metabolize phospholipids to phosphatidic acids (36)(37)(38) and so was an attractive candidate for involvement in membrane dissolution. However, F13 is important during morphogenesis for intracellular enveloped virus formation, and so its role in entry is difficult to study because without it very little EEV is produced (35).…”
Section: Resultsmentioning
confidence: 99%
“…Loss of the A56 or A33 protein did not affect this phenomenon. The F13 protein has sequence similarity to mammalian phospholipase (PL) D and has PL activity to metabolize phospholipids to phosphatidic acids (36)(37)(38) and so was an attractive candidate for involvement in membrane dissolution. However, F13 is important during morphogenesis for intracellular enveloped virus formation, and so its role in entry is difficult to study because without it very little EEV is produced (35).…”
Section: Resultsmentioning
confidence: 99%
“…Unsaturated fatty acids block HIV budding [126] Mycobactin mediates iron supply within macrophages [32] FA Affinity of HIV Gag protein is regulated by myristoyl switch [127] Presentation of glycerophospholipids, sulfolipids and mycolates via CD1 receptors [58,132,133] GP Golgi-derived viruses have different phospholipid (incl semilysobisphosphatidic acid) composition depending on the precise site of budding [7,128] HIV-like particle assembly is regulated by inositol phosphates [129] HIV-1 Gag targeting is regulated by PIP2 [130] Vaccinia virus envelope protein p37 has lipase activity [131] Nef transports cholesterol to site of HIV budding [134] ST Budding occurs from glycolipid-enriched membrane lipid rafts [8,[135][136][137] Table summarizing the reported involvement of lipids, both from the host as well as the pathogen, during various stages of host-pathogen interaction ( Fig. 1).…”
Section: Glmentioning
confidence: 99%
“…Some viruses have been shown to code for their own lipolytic enzymes. For example, the major envelope protein of vaccinia virus, p37, exhibits multiple lipolytic activities (5,7). It has been recently reported that a parvovirus contains a soluble PLA2 (sPLA2)-type activity encoded by the virus itself (14,35).…”
Section: Human Cytomegalovirus (Hcmv) Is a ␤ Herpesvirus That Causes mentioning
confidence: 99%